2016
DOI: 10.1111/plb.12460
|View full text |Cite
|
Sign up to set email alerts
|

CAX‐ing a wide net: Cation/H+ transporters in metal remediation and abiotic stress signalling

Abstract: Cation/proton exchangers (CAXs) are a class of secondary energised ion transporter that are being implicated in an increasing range of cellular and physiological functions. CAXs are primarily Ca2+ efflux transporters that mediate the sequestration of Ca2+ from the cytosol, usually into the vacuole. Some CAX isoforms have broad substrate specificity, providing the ability to transport trace metal ions such as Mn2+ and Cd2+, as well as Ca2+. In recent years, genomic analyses have begun to uncover the expansion o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
89
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 121 publications
(91 citation statements)
references
References 93 publications
(114 reference statements)
2
89
0
Order By: Relevance
“…The calcium signaling has been reported as an important mechanism for these kinds of stress sensing in plants (Tuteja and Sopory, 2008; Kader and Lindberg, 2010; Zhang et al, 2014a). Modulation in expression of CaCA superfamily genes such as CAXs and NCL has been earlier reported during abiotic stresses in various plant species (Wang et al, 2012; Li et al, 2016; Pittman and Hirschi, 2016b). Therefore, it becomes necessary to study the impact of these stresses on expression pattern of TaCaCA genes.…”
Section: Resultsmentioning
confidence: 76%
See 3 more Smart Citations
“…The calcium signaling has been reported as an important mechanism for these kinds of stress sensing in plants (Tuteja and Sopory, 2008; Kader and Lindberg, 2010; Zhang et al, 2014a). Modulation in expression of CaCA superfamily genes such as CAXs and NCL has been earlier reported during abiotic stresses in various plant species (Wang et al, 2012; Li et al, 2016; Pittman and Hirschi, 2016b). Therefore, it becomes necessary to study the impact of these stresses on expression pattern of TaCaCA genes.…”
Section: Resultsmentioning
confidence: 76%
“…The expression analysis is a method to predict the putative function of an unknown gene (Zeng et al, 2016). Further, CaCA superfamily genes are also reported to play vital role in plant development (Shaul et al, 1999; Cheng et al, 2005; Wang et al, 2012; Pittman and Hirschi, 2016b). Therefore, their expression was analyzed in various developmental stages of T. aestivum using high throughput transcriptome data (Pingault et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To determine the size and composition of the CAX gene family in A. halleri , genome sequence data (Briskine et al, ) and the first A. halleri reference transcriptome (Corso et al, ; Schvartzman et al, ) were explored (see Section 2 for further details about sequence retrieval). Sequence analyses revealed that A. halleri possesses six CAX genes, as is typical for many monocots and dicots (Pittman & Hirschi, ). The A. halleri CAX genes are phylogenetically closely related to the A. thaliana ones (Figure ).…”
Section: Resultsmentioning
confidence: 99%